Reliability and construct validity assessment of the student competency questionnaire among final year diploma students: A statistical analysis approach/ Nor Faezah Mohamad Razi and Norhayati Baharun - Mohamad Razi, Nor Faezah; Baharun, Norhayati (Universiti Teknologi MARA, Perak, 2024)
The university strives to provide students with a curriculum that is pertinent and taught by educators with exceptional delivery methods, in a stimulating and dynamic learning setting. The goal is for students to graduate as individuals who can make positive contributions to society, start their own businesses, and take on leadership roles in their professions. This research aims to develop the Student Competency Questionnaire (SCQ) and assess its reliability and validity. Using classical test theory, the evaluation focused on reliability, construct validity, and content validity. A postal questionnaire containing 49 items was distributed in October 2022 to a sample of 59 final year diploma students from various programs. Three experts in education, statistical modeling, and decision making evaluated the content validity of the scale. The Content Validity Index (CVI) for all constructs ranged from 0.96 to 1, exceeding the threshold of 0.70, indicating that the items are 'content valid.' Cronbach's alpha values showed a high level of internal consistency, all exceeding 0.90. Additionally, all items within each construct were highly related to one another, with correlations exceeding 0.30.This research demonstrates that the Pillar 1 education 5.0 @ Universiti Teknologi MARA (UiTM) frameworks effectively capture essential skills for students' academic and professional development, enhancing their employability. The focus on Personal, Adaptive, Digital, 21st Century, and Social competencies, along with student satisfaction, ensures students are equipped with diverse skills needed to thrive in dynamic environments. Overall, UiTM's approach prepares students for success in their future careers and personal lives.